85.2k views
0 votes
X-5y-z=-20

-2x-y-6z=25

-x-4y-z=-15
Solve by elimination

User George Sun
by
5.4k points

1 Answer

6 votes

Answer:

x = 0

y = 5

z = -5.

Explanation:

X-5y-z=-20

-2x-y-6z=25

-x-4y-z=-15

Add equation 1 and 3:

-9y - 2z = -35 .......... A

Multiply the first equation by 2:

2x - 10y - 2z = -40

Now add this to equation 2:

-11y -8z = -15.............B

Now multiply equation A by -4:

36y + 8x = 140.........C

Add equations B and C:

25y = 125

y = 5.

Substitute for y in equation A:

-9*5 - 2z = -35

2z = -45 + 35 = - 10

z = -5.

Now find x by substituting for y and z in the first equation:

x - 5(5) - (-5) = -20

x - 20 = -20

x = 0.

User Mibu
by
4.8k points